Understanding the Impact of Stent and Scaffold Material and Strut Design on Coronary Artery Thrombosis from the Basic and Clinical Points of View - Atsushi Sakamoto; Hiroyuki Jinnouchi; Sho Torii; Renu Virmani; Aloke V. Finn (Bioengineering, 2018)
The technology of percutaneous coronary intervention (PCI) is constantly being refined in order to overcome the shortcomings of present day technologies. Even though current generation metallic drug-eluting stents (DES) perform very well in the short-term, concerns still exist about their long-term efficacy. Late clinical complications including late stent thrombosis (ST), restenosis, and neoatherosclerosis still exist and many of these events may be attributed to either the metallic platform and/or the drug and polymer left behind in the arterial wall. To overcome this limitation, the concept of totally bioresorbable vascular scaffolds (BRS) was invented with the idea that by eliminating long-term exposure of the vessel wall to the metal backbone, drug, and polymer, late outcomes would improve. The Absorb-bioabsorbable vascular scaffold (Absorb-BVS) represented the most advanced attempt to make such a device, with thicker struts, greater vessel surface area coverage and less radial force versus contemporary DES. Unfortunately, almost one year after its initial approval by the U.S. Food and Drug Administration, this scaffold was withdrawn from the market due to declining devise utilization driven by the concerns about scaffold thrombosis (ScT) seen in both early and late time points. Additionally, the specific causes of ScT have not yet been fully elucidated. In this review, we discuss the platform, vascular response, and clinical data of past and current metallic coronary stents with the Absorb-BVS and newer generation BRS, concentrating on their material/design and the mechanisms of thrombotic complications from the pre-clinical, pathologic, and clinical viewpoints.